Efficacy and safety of abacavir/lamivudine plus rilpivirine as a first-line regimen in treatment-naïve HIV-1 infected adults - Ho, Sharlene (2021)
Background: The anti-retroviral combination of abacavir/lamivudine plus rilpivirine (ABC/3TC/RPV) is not recommended by international guidelines as the first-line regimen. However, it is potent, well-tolerated, and affordable, especially in resource-limited settings. This study evaluates the efficacy and safety of ABC/3TC/RPV as an initial regimen for treatment-naïve HIV-1 infected patients. Methods: A retrospective study was conducted in the largest HIV care centre in Singapore, with data collected June 2011 to September 2017. All treatment-naïve HIV-1 infected adults prescribed ABC/3TC as part of their initial anti-retroviral therapy regimen were included. The third drug was a non-nucleoside reverse-transcriptase inhibitor (NNRTI) such as RPV or efavirenz (EFV ), or boosted protease-inhibitor (PI). Patients were followed up for 48 weeks. The primary end-point was the percentage of patients achieving virologic suppression, analysed using on-treatment analysis. Secondary outcomes included CD4-count change, treatment discontinuation and treatment-related adverse events. Results: 170 patients were included in the study, 66 patients in the RPV group, 104 patients in the comparator group (EFV or boosted PI). 96% (n =24) in the RPV group and 87% (n =26) in the comparator group achieved viral suppression at 48 weeks (p =0.28). Median (interquartile range) time to viral suppression was similar: 17 (14–24) weeks in the RPV group, and 21 (13–26) weeks in the comparator group. There were no statistically significant differences in the CD4 count between the two groups. 14% (n =9) of patients on RPV discontinued treatment before 48 weeks, com-pared to 30% (n =31) from the comparator group (p =0.053). Of these, 23 discontinuations were due to drug adverse effects, and only 1 attributed to RPV (p < 0.01). One patient in each group had virologic failure. Conclusion: RPV is effective, safe and considerably more tolerable than compared to NNRTI or boosted PI in ABC/3TC-containing regimens for treatment-naïve patients. It offers an affordable and attractive option, especially in resource-limited settings.